(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
There has been upsurge in the incidents of religious violence in Nigeria and to a large extent; the country is no longer safe for the citizens and the investors. Based on this premises, this paper x-rayed historical background to religious crises, causes of religious crises, religion and development, and the implications of religious crises on national development. Survey research method was used to asses this situation and empirical results were found. From these results, it was discovered that, religion was the genesis of ethno- political crisis that infiltrates the present day Nigeria. This paper posits that religion which is supposed to be a unifying factor has contributed immensely to division, acrimony and all sorts of evil that permeates our contemporary Nigeria. However, it was noted in the paper that, many of the crises considered to be religious crises in Nigeria were actually political and tribal crises. To stem the tide of religious violence in Nigeria will be a herculean task because; the country is a fertile land for all forms of religion fundamentalists. Also, religion has been politicized in the county despite the fact that the country is a secular state. Finally, this work posits that, religious crises run counter to the tenets, teachings and ethical values of the three major religions which are in practice in the country. Meanwhile, religious fanatics and fundamentalists who originated and still promote religious crises in Nigeria violate religious tenets, ethical codes and teachings from the holy books. This paper concludes that, religious leaders as a result of their influence on the adherents must intensify efforts in sensitizing them on the dangers of crises in the country. Equally, religious leaders should desist from being an instrument of destruction in the hands of the political leaders.